2005
DOI: 10.1016/j.jfluchem.2004.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phosphate-type fluorocarbon–hydrocarbon hybrid surfactants and their adsorption onto calcium hydroxyapatite

Abstract: Five novel phosphate-type hybrid surfactants, C m F 2m+1 C 6 H 4 CH[OPO 2 (OC 6 H 5 )Na]C n H 2n+1 (FmPHnPPhNa: m = 4, 6, 8; n = 3, 5; C 6 H 4 = p-phenylene, C 6 H 5 = phenyl), have been synthesized. When compared with sulfate-type hybrid surfactants, C m F 2m+1 C 6 H 4 CH(O-SO 3 Na)C n H 2n+1 (C 6 H 4 = p-phenylene), the new hybrid surfactants are found to have comparable abilities to lower surface tension of water. The critical micelle concentrations of FmPHnPPhNa follow Klevens rule and their occupied areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…FmPHnS are expected to be a good emulsifier for making aqueous fluorocarbon paints because they are able to emulsify fluorocarbon/water/hydrocarbon systems (6). The present authors have also reported that the synthesized hybrid surfactants form long-life micelles detected by NMR (7) and abnormally highly viscous solutions at about 10 wt% and 36 (8)(9)(10)(11)(12), and have a human tooth reformability for the prevention of its decay (13). These properties are characteristic of the hybrid surfactants and cannot be developed by mixed systems of fluorocarbon and hydrocarbon surfactants.…”
supporting
confidence: 51%
“…S N (13) Here, N is the aggregation number and S and S N denote respectively monomer and micelle. The equilibrium constant K is given by Eq.…”
Section: Nsmentioning
confidence: 99%
“…The synthesis of phosphate-type hybrid surfactants has been described elsewhere (10). They are denoted as FmPHnPPhNa in ref.…”
Section: Experimental 1 Materialsmentioning
confidence: 99%
“…A series of novel phosphate-type hybrid surfactants ( Fig. 1(a)) have been synthesized quite recently (10). This type of surfactants is expected to be useful in the field of dentistry, because they would adsorb strongly on teeth due to the phenyl phosphate group and would keep the teeth clean owing to their hydrophobic and lipophobic nature.…”
mentioning
confidence: 99%
See 1 more Smart Citation